High levels of lipoprotein(a) are associated with the severity of coronary disease in patients with acute myocardial infarction. Data from the RICO survey. (25th November 2020) - Farnier, M; Yao, H; Hounton, N; Maza, M; Chague, F; Bichat, F; Beer, J.C; Lagrost, L; Masson, D; Cottin, Y; Zeller, M
Abstract: Background: High level of Lipoprotein(a), Lp(a), is a well-recognised independent risk factor for atherosclerotic cardiovascular disease (ASCVD). However, limited data are available on the prevalence of high Lp(a) levels and on the threshold associated to coronary artery disease (CAD) burden in patients with acute myocardial infarction (MI). Methods: We aim at assessing CAD burden in 651 consecutive patients hospitalized for an acute MI from January 2019 to September 2019 who underwent coronary angiography. Patients characteristics and angiographic features were compared for patients with Lp(a) <50 mg/dL (normal), ≥50 mg/dL (high) and >80 mg/dL (i.e >90th percentile) (very high). Results: The prevalence of Lp(a) ≥50 mg/dL was elevated (19.0%) and 65 patients (10.0%) were in the >90th percentile. Median (IQR) age was similar across the 3 groups (normal: 68 (59–79)y; high: 74 (63–80)y; very high: 71 (57–82)y, p=0.239). When compared with patients with normal Lp(a), patients with very high levels (≥80 mg/dL) had higher prevalence of personal history of ASCVD (29 vs 16%, p=0.021) and family history of CAD (37 vs 19%, p=0.005), and were more frequently women (43 vs 29%, p=0.009). At coronary angiography, patients with very high Lp(a) levels had increased extent of CAD (Median SYNTAX score 17 (5–25) vs 10 (5–17), p=0.002) and more frequent multivessel disease (69 vs 54%, p=0.02). Conclusion: Among real world patients hospitalized for an acute MI, Lp(a) levels >80 mg/dL are associated with an increased CAD burden and this threshold identifies a subset of patients with features of high ASCVD risk. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): ARS Bourgogne Franche Comté; CHU Dijon Bourgogne